Impact of Low-Burden TP53 Mutations in the Management of CLL - Lazarian, Gregory; Cymbalista, Florence; Baran-Marszak, Fanny (Frontiers in Oncology, 2022)
In chronic lymphocytic leukaemia (CLL), TP53 abnormalities are associated with reduced survival and resistance to chemoimmunotherapy (CIT). The recommended threshold to clinically report TP53 mutations is a matter of debate given that next-generation sequencing technologies can detect mutations with a limit of detection of approximately 1% with high confidence. However, the clinical impact of low-burden TP53 mutations with a variant allele frequency (VAF) of less than 10% remains unclear. Longitudinal analysis before and after fludarabine based on NGS sequencing demonstrated that low-burden TP53 mutations were present before the onset of treatment and expanded at relapse to become the predominant clone. Most studies evaluating the prognostic or predictive impact of low-burden TP53 mutations in untreated patients show that low-burden TP53 mutations have the same unfavourable prognostic impact as clonal defects. Moreover, studies designed to assess the predictive impact of low-burden TP53 mutations showed that TP53 mutations, irrespective of mutation burden, have an inferior impact on overall survival for CIT-treated patients. As low-burden and high-burden TP53 mutations have comparable clinical impacts, redefining the VAF threshold may have important implications for the clinical management of CLL.